Here's the question you clicked on:
BelleFlower
Please wait for image! Logarithms question
loga - logb = log(a/b) loga + logb = log(a*b) x=log(e^x) logx=logy => x=y now help urself
|dw:1356767087691:dw| Can you think of the next step?
(That thing in the denominator of the parentheses is a 'b' -- sorry for sloppy artwork)
I'm still not sure how to continue actually... :/ @LogicalApple
Consider e and ln as inverse functions. I.e., ln(e^x) = x, and e^(ln(x)) = x. Try raising e to the power of both sides. For example, on the left side you would get e^(ln K) = K
And whatever you do to one side you have to do to the other
What are inverse functions? Sorry i don't really get it
An inverse function cancels out the original function. Like square and square root functions are inverses of each other. Multiplication and division are inverses. Here, e and ln are inverses. That is why when we have e^(ln K), the e and ln cancel leaving only K.
But I am supposed to solve this just using the power, product, quotient laws and the change-of-base law....
But I see there is an 'e' in the answer, so you must be able to use the function.
I will present a solution. Tell me if you have any questions about it. One sec.